2012
DOI: 10.1021/es3005199
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls of Cadmium Desorption during CO2 Leakage

Abstract: Geologic carbon sequestration represents a promising option for carbon mitigation. Injected CO(2), however, can potentially leak into water systems, increase water acidity, and mobilize metals. This study used column experiments to quantify the effects of environmental controls on cadmium desorption during CO(2) leakage in subsurface systems without ambient flow. Results show that fast leakage rates are responsible for earlier and larger amounts of Cd desorption. Long weathering time of Cd laden clay leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 63 publications
(123 reference statements)
1
43
0
Order By: Relevance
“…This means that dissolution of calcite induced by CO 2 is dissociated from potential remobilization of sorbed Cd and Cu. The role of calcite in Cd immobilization onto sediment (illite and calcite) was also confirmed by Frye et al (2012), who concluded that calcite contents as low as 10% can mitigate the effect of pH reduction and that Cd release and sorption is strongly pH-dependent.…”
Section: Laboratory Experimentsmentioning
confidence: 70%
See 1 more Smart Citation
“…This means that dissolution of calcite induced by CO 2 is dissociated from potential remobilization of sorbed Cd and Cu. The role of calcite in Cd immobilization onto sediment (illite and calcite) was also confirmed by Frye et al (2012), who concluded that calcite contents as low as 10% can mitigate the effect of pH reduction and that Cd release and sorption is strongly pH-dependent.…”
Section: Laboratory Experimentsmentioning
confidence: 70%
“…This can be explained by a significant change in the surface charge of the goethite after CO 2 intrusion, assuming that surface charge is strongly dependent on pH as it is widely described in the literature. Frye et al (2012) investigated the effect of salinity on desorption behaviour in a column experiment. Besides a higher solubility of CO 2 in low ionic strength solutions with a lower pH, they showed that desorption is enhanced by high ionic strength.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Possible leakage pathways include annular spaces or degraded zones between cement and rock, between the cement and the casing, or the cement plug itself [Celia and Bachu, 2003]. Leakage of CO 2 through these pathways into shallower formations and to the surface can potentially impose significant risks to water quality and ecosystems [Frye et al, 2012;Hofmann et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The behaviors of the injected CO 2 and its effects on the chemical changes of groundwater quality have been extensively proposed and discussed through laboratory (Little and Jackson, 2010;Lu et al, 2010;Frye et al, 2012;Terzi et al, 2014) and field tests (Kharaka et al, 2010;Cahill et al, 2014). It has been understood that gaseous CO 2 or CO 2 -infused groundwater has potential to degrade the shallowdepth groundwater quality (Bachu, 2008;Newmark et al, 2010;Harvey et al, 2012;Siirila et al, 2012).…”
Section: Behavior Of Injected Co 2 and Its Effects On Groundwater Quamentioning
confidence: 99%